Manajemen Pendistribusian Zakat Produktif Pada Badan Amil Zakat Nasional (BAZNAS) Kota Padang Panjang - Amri Effendi; Widi Nopiardo; Rizal Fahlefi; Fitri Dayana (IAIN Batusangkar, 2021)
Useful zakat is a zakat circulation model which can make mustahiq produce something persistently, with zakat resources that have been gotten. This review means to recognize and portray the dispersion of useful zakat conveyed by BAZNAS Padang Panjang City to the local area to increment mustahiq pay and to distinguish and depict the deterrents looked by BAZNAS Padang Panjang City in appropriating the useful zakat. The sort of exploration that scientists use is field examination or field research. The exploration strategy utilized is illustrative subjective technique. The circulation of useful zakat completed by BAZNAS Padang Panjang City depends on the Padang Panjang Makmur Program where the general execution has been working out positively. Be that as it may, BAZNAS Padang Panjang City is as yet encountering issues in the conveyance, remembering the absence of HR for overseeing mustahiq who get useful zakat, overall the mustahiq zakat in Padang Panjang City has gotten useful zakat, so from the SOP side of BAZNAS they deferred the dispersion due to mustahiq zakat. can just get zakat 1 (once) in 3 years except if their business encounters a catastrophe